2018
DOI: 10.1002/glia.23322
|View full text |Cite
|
Sign up to set email alerts
|

Draper‐mediated JNK signaling is required for glial phagocytosis of apoptotic neurons during Drosophila metamorphosis

Abstract: Development of the central nervous system involves elimination of superfluous neurons through apoptosis and subsequent phagocytosis. In Drosophila, this occurs mainly during three developmental stages: embryogenesis, metamorphosis and emerging adult. Two transmembrane glial phagocytic receptors, SIMU (homolog of the mammalian Stabilin-2) and Draper (homolog of the mammalian MEGF10 and Jedi), mediate glial phagocytosis of apoptotic neurons during embryogenesis. However, less is known about the removal of apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 48 publications
2
29
0
Order By: Relevance
“…Confirming antibody specificity, cortex glial RNAi-mediated knockdown of all Drpr isoforms results in a 49% decrease in Drpr levels (Figure 3F), and cortex glial RNAi-mediated knockdown of Drpr-I, the isoform that promotes debris clearance, results in a 53% decrease (Figures 3B and 3F;Logan et al, 2012). As expected, drpr nulls exhibit a vast excess of apoptotic debris (Figures 3L and 3M) (Hilu-Dadia et al, 2018). And in line with a previous report (Etchegaray et al, 2016), we find that Drpr functions specifically in cortex glia since cortex-glial-specific knockdown of all Drpr isoforms ( Figures 3K-3N Figures 3E and 3G).…”
Section: Toll-6-foxo Signaling Regulates Draper Transcription In Cortsupporting
confidence: 73%
See 1 more Smart Citation
“…Confirming antibody specificity, cortex glial RNAi-mediated knockdown of all Drpr isoforms results in a 49% decrease in Drpr levels (Figure 3F), and cortex glial RNAi-mediated knockdown of Drpr-I, the isoform that promotes debris clearance, results in a 53% decrease (Figures 3B and 3F;Logan et al, 2012). As expected, drpr nulls exhibit a vast excess of apoptotic debris (Figures 3L and 3M) (Hilu-Dadia et al, 2018). And in line with a previous report (Etchegaray et al, 2016), we find that Drpr functions specifically in cortex glia since cortex-glial-specific knockdown of all Drpr isoforms ( Figures 3K-3N Figures 3E and 3G).…”
Section: Toll-6-foxo Signaling Regulates Draper Transcription In Cortsupporting
confidence: 73%
“…Third, Drpr overexpression fully rescues increased Dcp-1 accumulation in pathway mutants. Since Drpr is the primary engulfment receptor in the CNS (Hilu-Dadia et al, 2018;Tasdemir-Yilmaz and Freeman, 2014), these results demonstrate that phagocytosis is specifically impaired in the mutants. Fourth, pathway over-activation results in reduced apoptotic debris, consistent with the hypothesis that this ''priming'' pathway normally accelerates debris clearance.…”
Section: Discussionmentioning
confidence: 66%
“…While previous studies have demonstrated that JNK signaling is upregulated in glia in response to neuronal injury and plays a role in promoting glial phagocytosis of neurons during development, the role of JNK signaling in gliogenesis has been largely unexplored [ 48 50 ]. Studies in the embryo showed that mutation of zinc finger homeodomain 1 ( zfh1 ) promoted apoptosis of ePG10 in a JNK-dependent manner, although Zfh1 was expressed in all ePGs [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a specific cell type likely differs only in the expression of the limited number of genes which confer a new function to it [10,11]. In this study, we used a publicly available expression profile of 55,000 single cells of Drosophila optic lobe in order to find novel molecular markers for specific cell types, following by experimental confirmation of the predicted results.…”
Section: Introductionmentioning
confidence: 96%